Development of well reception to reduce rain surface surface in Sunggal village right Deli Serdang district - Tarigan, J.; Roesyanto; Sembiring, R.A.; Pulungan, M.A.; Ananta, A. (Talenta Publisher, 2019)
Water catchment areas are very important to reduce surface runoff that enters the drainage, but the rise of housing development results in damage to the water catchment area. Development of settlements, offices, educational buildings, and other buildings often do not pay attention to areas that should be open green land. Land cover causes a large infiltration to be reduced when it rains, thereby increasing surface runoff which can result in inundation or flooding. One village that is increasingly crowded with settlements is the right sunggal village in the Deli Serdang district. The main problem in the village of Sunggal Kanan, especially the Gusti Wijaya University Foundation, which is a service partner, is the lack of open land in the foundation complex as a water catchment zone. The solution offered in this program is in the form of infiltration well construction. This method utilizes wells as a water catchment container when it rains. With this infiltration well, rainwater runoff can be reduced.